Outcomes of Alvimopan Use in Laparoscopic Intra-abdominal Surgery: A Retrospective Review - Aamir A. Kokan; Sahil Sheth; Katherine Rogers (University of Minnesota Libraries Publishing, 2021)
Background: Postoperative ileus is a transient cessation of bowel motility, occurring after bowel resection, characterized by abdominal distension and pain, nausea, vomiting, and an accumulation of gas/fluids in the bowel. It is associated with a greater incidence of postoperative morbidity and increased length of stay or readmission. Alvimopan, a novel peripheral mu receptor antagonist, is indicated for preventing postoperative ileus in patients undergoing intra-abdominal surgery or bowel resection. The objective of this study was to assess the impact of alvimopan use in laparoscopic abdominal surgeries. Objective: To assess alvimopan use's impact in laparoscopic abdominal surgeries. Methods: A retrospective chart review was conducted of 84 patients who underwent laparoscopic procedures that received alvimopan (September 1, 2018 to October 31, 2018) and compared to patients that did not receive alvimopan (May 1, 2018 to June 30, 2018, due to a national shortage of the medication). The primary outcome was the rate of postoperative ileus. Secondary outcomes included rate of 30-day readmission, length of stay (LOS), postoperative opioid and laxative use, time to initiation of oral diet, and return of bowel function (ROBF) as demonstrated by recorded bowel movement. Results: There was no statistical difference observed in primary outcome of postoperative ileus between alvimopan and no alvimopan groups (2.7% vs 4.3%, p=1). Secondary outcomes such as length of stay (5.4 days vs 5.4 days, p=0.49), length of postoperative stay (5 vs 4.9, p=0.44), days to oral diet (0.9 vs 0.4, p=0.16), time to BM (1.8 vs 2.2, p=0.32), and 30-day readmission were also similar between the two groups. Conclusion: The similar outcome profiles in all primary and secondary outcomes do not support the use of alvimopan in the setting of laparoscopic intra-abdominal surgery.